Soil water movement modelling in hapllicc luvisols (HMm) and albi hapllic luvisols (HMl) under Slovak climatic conditions - Tóthová, Iveta; Igaz, Dušan; Antal, Jaroslav (Journal of Environmental Engineering and Landscape Management, 2007)
The aim of the research paper is simulation by the Global Model on the basis of investigation of Slovak Agricultural University (SAU) on two localities (Kolínany and Malanta). The soil moisture was measured by a time domain transmissometry instrument and compared with simulated outputs of the Global Model on Kolínany locality. Measurement of the soil moisture using the gravimetric method was applied on Malanta locality. Sugar beet was grown in Kolínany and, on the other hand, there was no plant on Malanta soil during the experiment. The experiment took three years (2002–2004). Measured and simulated courses of water content were consequently tested by correlation analysis in MS Excel. Result differences between simulated and measured values should reach according to 15% difference at least 80% of equality. Correlation between measured and simulated values had a high significance on Kolínany locality (in the range of 0,62–0,90) Equality between measured and simulated values was from 33% to 75% according to difference of 15%.Dirvožemio drėgmės judėjimo modeliavimas Slovakijos klimato sąlygomis taikant hapllicc luvisols (HMm) ir albi hapllic luvisols (HMI) modeliusSantrauka. Tyrimo tikslas yra dviejų vietovių (Kolíňany ir Malanta) modeliavimas taikant globalųjį modelį, remiantis Slovakijos žemės ūkio universiteto (SŽŪU) tyrimų baze. Dirvožemio drėgmė buvo išmatuota ir palyginta su gautais taikant globalųjį modelį Kolíňany vietovės modeliavimo duomenimis. Dirvožemio drėgmė matuota taikant gravimetrinį metodą Malanta vietovėje. Cukriniai runkeliai augo Kolíňany, o Malanta vietovėje nebuvo jokių augalų. Eksperimentas truko trejus metus (2002–2004), todėl išmatuoti ir sumodeliuoti vandens sudėties šaltiniai buvo testuojami koreliacine analize Excel programa. Rezultatų tarp sumodeliuotų ir išmatuotų verčių skirtumai turėtų siekti 15 % skirtumą mažiausiai 80 % lygybei. Koreliacija tarp išmatuotų ir sumodeliuotų verčių buvo reikšminga Kolíňany vietovei (santykiu 0,62–0,90). Lygybė tarp išmatuotų ir sumodeliuotų verčių buvo nuo 33 % iki 75 % pagal 15 % skirtumą.Reikšminiai žodžiai: dirvožemis, vandens sudėtis, drėgmė, matematinis globalusis modelis, koreliacija, gravimetrinis metodas.Моделирование перемещения грунтовой влаги в климатических условиях словакии с помощью моделей hapllicc luvisols (HMm) ir albi hapllic luvisols (HMl)Резюме. Целью исследования было моделирование перемещения грунтовой влаги двух местностей (Колинани и Маланта) с использованием Глобальной модели на базе исследований Словацкого университета сельского хозяйства. Влажность грунта была измерена и сравнена с полученными с помощью Глобальной модели данными для местности Колинани. Измерение влажности грунта по гравиметрическому методу осуществлялось для местности Маланта. Во время эксперимента в Колинани выращивалась сахарная свекла, в то время как в Маланте растений не было. Эксперимент длился три года (2002–2004), поэтому измеренные и смоделированные источники состава воды тестировались с помощью корреляционного анализа по программе Excel. Разница результатов измеренных и смоделированных величин составила 15 % для 80 % равенств. Корреляция между измеренными и смоделированными величинами наиболее значительной была для местности Колинани (0,62–0,90). Равенство измеренных и смоделированных величин составило от 33 % до 75 % при 15%-ой разнице.Ключевые слова: грунт, состав воды, влажность, математическая Глобальная модель, корреляция, гравиметрический метод.First Published Online: 14 Oct 2010